SIGNIFICANCE OF VALUE CHAIN ANALYSIS FOR CHILLI - THE CASE OF KARNATAKA CHILLI MARKET - SANDEEP K. T* and NAVITHA THIMMAIAH, (The Journal of Research ANGRAU, 2020)
Value chain analysis for chilli in Karnataka revealed that fixed costs formed a smaller proportion of thetotal cost of dry chillies processing (ranging from 13.17% in the case of medium size processing units to16.98%in the case of large units). However, large units had relatively greater proportion of fixed costs as they mechanizedmost of the stages of processing in order to reap economies of scale. Among the various components ofvariable costs, raw material (i.e. the dry chillies) accounted for the highest percentage, ranging from 13.39% inrespect of large processors to 18.82% in the case of small size processors.In all the three value chainsidentified, the value addition cost in chain 1 (VAC 1) was the highest with Rs.380 and the lowest is in case ofVAC2 with Rs.267. Among the various persons involved in the value chain, the wholesaler and processorplayed an important role; the former being important in grading, packing and transportation; and the latterbeing crucial in converting raw chillies into value-added products. The retailer was only involved in the task ofmoving the produce (raw or processed) to the consumer.